Penerapan Manajemen Risiko Terhadap Kinerja Keuangan Bank Syariah Di Indonesia - Nataline Simanjuntak; Irma Siagian; Elisabeth Tamara Ratu Hutauruk; Irna Della Br Ginting; Bona Vintura Suyana Pandiangan (Sharing: Journal of Islamic Economics Management and Business, 2026)
Risk management is a crucial aspect in maintaining stability and improving the financial performance of Islamic banks. Islamic banking operations are inherently subject to various risks. Suboptimal risk management can impact bank health and undermine public trust in Islamic financial institutions. This study aims to analyze the implementation of risk management and its relationship to the financial performance of Islamic banks in Indonesia. The method used is descriptive qualitative, utilizing secondary data obtained from reports from the Financial Services Authority (OJK), Bank Indonesia, scientific journals, books, and various relevant literature sources. Data collection techniques were conducted through literature and documentation studies. The study results indicate that effective risk management implementation can assist Islamic banks in controlling problem financing, maintaining liquidity levels, increasing profitability, and strengthening financial stability. Furthermore, sound risk management supports increased public trust and the competitiveness of Islamic banks amidst the increasingly dynamic development of the financial industry. Thus, risk management not only functions as a risk control mechanism but also plays a vital role in supporting the well-being and financial performance of Islamic banks.